AN ANALYSIS OF THE STUDENTS’ ABILITY IN COMPREHENDING RECOUNT TEXT AT THE SECOND GRADE OF SMP MUHAMMADIYAH 1 PEKANBARU - Najmatul Fahli Fahli; Mahdum '; Fakhri Ras Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was designed to describe the students’ ability in comprehending recount text. The aim was to find out students ability in comprehending the text. This descriptive research took place in SMP Muhammadiyah 1 Pekanbaru from March to April 2015. The sample was 40 students from VIII2 class that took by using cluster random sampling. In collecting the data, there were 30 questions that included in this test. The duration time for doing the test was 40 minutes. The data was analyzed by calculating the students’ score individually and finding out the mean score. The students’ score classified into four level mastery; they are: poor, poor to average, average to good, and good to excellent. The data was presented by using graphic. Based on the result finding of this research, the students’ ability in comprehending recount text at second grade of SMP Muhammadiyah 1 Pekanbaru was in poor to average level. Meanwhile, the mean score of the whole students’ scores was 52.6. Keywords: Students’ Ability, Comprehending Recount Text